The relationship between agility and orientation ability in judoka children - Alper Tunga Peker; Mine Taskın; Halil Taskın; Alparslan Unveren (Selcuk University, 2017)
Agility can be defined as the ability which allows to act and alter aspect quickly and effectively during a stimulation such as the movement of the ball or the movement of the rival athletes. Exercises which comprise agility drills are important components of training for many sports. Agility is one of significant components which contributes that athlete's exhibit optimal performance. There are several components that contributes to agility, such as training level, reaction time, strength, power, decision making and experience Orientation allows players and athletes to localize and identify the position and motion of his body or of a moving object (rival, teammate), as regards the space. The aim of this study was to determine the relationship between agility and orientation. Subject characteristics were as follows: age = 10.34 ± 1.40 years, height = 1.40 ± 0.08 m, and weight = 33.50 ± 9.25 kg. The sample included 67 judoka children in Turkey. The Pro-Agility test was set up and administered using the protocol outlined. Numbered medicine ball run test was used to determine orientation ability of the subjects. The study is observed that the orientation ability did affect the agility performance (p lt;0.05). Orientation ability (r=-0.365) showed a positively significant (p lt;0.05) relationship. In conclusion, it is considered that the orientation ability did affect the agility performance and it can be said that the agility performance will also improve when the orientation ability of the athlete is developed.